Explaining the Success of a Young Gaming Start-up : A Case Study of Warhorse Studios - Novák, Michal; Svačina, Pavel, 1979-; Kubíček, Aleš; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2023)
The survival of early-stage companies is uncertain. Their survival and success are often linked to obtaining a substantial financial investment. This in-depth single case study examines how and why an early-stage start-up from the video game industry obtains venture investment from an independent equity investor and offers deeper and more comprehensive insights into the success mechanism of gaming start-ups. The study (i) generally confirms the previous findings that certain theoretical factors increase the likelihood of success, (ii) argues that accumulating these factors, rather than their presence, is essential for a start-up to be substantially funded, (iii) shows that the expected market response is crucial and significantly outweighs the other factors, (iv) conceptualize the reasons for start-ups’ success as a reduction of two main types of risk – development risk and sales risk, (v) confirms the catalytic role of crowdfunding in obtaining significant equity funding.
Vedoucí práce: Pavel Svačina
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: účetnictví a finanční řízení podniku [obor disert. práce]; disertace; dissertations